Influence of Different Ambient Temperatures on the Thermal Properties of Fiber-Reinforced Structural Lightweight Aggregate Concrete - Shafigh P.; Hafez M.A.; Che Muda Z.; Beddu S.; Zakaria A.; Almkahal Z. (MDPI, 2023)
This study reports the influence of different climatic ambient temperatures on the thermal properties of fiber-reinforced lightweight aggregate concrete (LWAC). Lightweight expanded clay aggregates (LECA) with steel (ST) and polypropylene fibers were used in the mix proportions. The steady-state thermal test was performed on concrete samples at the oven-dry state with the measurement taken at six different climatic ambient temperatures of 0?C, 10?C, 20?C, 30?C, 40?C, and 50?C. The results show a linear dependence of thermal conductivity, specific heat, thermal diffusivity and thermal effusivity of fiber-reinforced LWACs against the different ambient temperatures. These ambient temperature variations are discussed as a function of the thermal properties of fiber-reinforced LWAC. The thermal conductivity and thermal diffusivity decrease linearly between 0?C and 50?C, whilst the specific heat and thermal effusivity increase linearly between 0?C and 50?C. Equations with strong correlations to predict thermal properties of fiber-reinforced LWAC were proposed based on the results of this study. The significance of this research is to propose the dynamic ambient temperature-dependent thermal properties equations that can be used in the energy analysis of the buildings. 2022 by the authors. Licensee MDPI, Basel, Switzerland.